The solvability criterion of cubic equations over p-adic field - Mukhamedov, Farrukh; Saburov, Mansoor (IIUM Press, 2012)
Unlike real numbers, in general, the cubic equation is not necessary to have a solution over p-adic field. Therefore, in this paper, we provide a solvability criterion for a cubic equation in Z^* p. In principal, the Cardano method is not always applicable for such kind of equations. Moreover, the numbers of solutions of the cubic equation in domains Z^*_p; are provided.